PENGEMBANGAN MEDIA BELAJAR PJOK PADA MATERI SENAM LANTAI (ARTISTIK) - Zulbahri, Zulbahri; Astuti, Yuni; ., Erianti; ., Pitnawati; ., Damrah (Universitas Pendidikan Ganesha, 2020)
This research is motivated by the limited development of learning media for the subjects of Physical Education, Sports and Health on floor exercise (artistic) material, especially for schools in the regions. This study aims to produce a learning media product for students and students in learning gymnastics. The subjects or samples of this research were FIK UNP students who attended basic and advanced / learning gymnastics courses with a total of 12 people for small group subject trials and 15 people for field trials. The data used in this research are qualitative and quantitative data. Qualitative data in this study is data obtained through validation from material experts, media experts, while quantitative data in this study were obtained through assessment questionnaires which were analyzed with descriptive statistics.This research was conducted using